A Holistic Approach to Cardiometabolic and Infectious Health in the General Population of Reunion Island: The REUNION Study - Mohammad Ryadh Pokeerbux; Patrick Mavingui; Patrick Gérardin; Nelly Agrinier; Erick Gokalsing; Olivier Meilhac; Maxime Cournot (Springer, 2024)
Abstract Introduction Reunion Island is a French overseas department in the South West Indian Ocean with a unique multi-ethnic population. Cardiovascular diseases are the most common chronic conditions with higher prevalences of hypertension and diabetes compared to mainland France. Moreover, Reunion Island is particularly exposed to vector-borne diseases such as chikungunya and dengue. Our objective is to describe the prevalence of cardiometabolic and infectious diseases in Reunion Island and explore causal mechanisms linking these diseases. Methods The REUNION study is an ongoing French prospective study. From January 2022, 2,000 consenting participants (18-68 years old) are being recruited from the general population according to polling lists and random generation of cellphone number. Baseline examination consists of (i) general health examination, assessment of cardiovascular risk factors, markers of subclinical atherosclerosis, bronchial obstruction, neuropathic and autonomic dysfunction, (ii) questionnaires to determine sociodemographic characteristics, diet, exposure to vector-borne diseases, mental health and cognitive functions, social inequalities in health and ethnic origins, (iii) biological sampling for determination of cardiovascular risk factors, seroprevalence of infectious diseases, innovative lipid biomarkers, advanced omics, composition of intestinal, periodontal and skin microbiota, and biobanking. Conclusions The REUNION study should provide new insights into the prevalence of cardiometabolic and infectious diseases, as well as their potential associations through the examination of various environmental pathways and a wide range of health aspects.